Careers of PhD-prepared nurses: A global survey - Van Dongen, Lisa; Hafsteinsdóttir, Thóra B.; Leino-Kilpi Helena; Suhonen, Riitta (Elsevier BV, 2026)
Background
PhD-prepared nurses uniquely contribute to nursing by conducting research required to address challenges in healthcare and nursing. However, there is limited understanding on the careers of PhD-prepared nurses.
Purpose
To describe careers, factors related to careers, and recommendations for the careers of PhD-prepared nurses.
Methods
A global cross-sectional study was conducted using a convenience sample of individuals with a Doctor of Philosophy degree in nursing science. A self-developed survey instrument was used.
Findings
Of the 1,308 PhD-prepared nurses, most worked in research and teaching positions. Most reported positions for PhD-prepared nurses being available within their organizations. Mentoring and development of career pathways, including clinical–academic positions, were recommended.
Discussion
PhD-prepared nurses pursue a variety of careers after the doctorate. Development of career pathways with positions with time for research, opportunities for professional development, and mentoring can support careers. Future research is suggested to support knowledge development in the field.